2005
DOI: 10.1074/jbc.m506086200
|View full text |Cite
|
Sign up to set email alerts
|

Microautophagic Vacuole Invagination Requires Calmodulin in a Ca2+-independent Function

Abstract: Microautophagy is the uptake of cytosolic compounds by direct invagination of the vacuolar/lysosomal membrane. In Saccharomyces cerevisiae microautophagic uptake of soluble cytosolic proteins occurs via an autophagic tube, a highly specialized vacuolar membrane invagination. Autophagic tubes are topologically equivalent to the invaginations at multivesicular endosomes. At the tip of an autophagic tube, vesicles (autophagic bodies) pinch off into the vacuolar lumen for degradation. In this study we have identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 82 publications
3
40
0
2
Order By: Relevance
“…Vtc-Cmd1p interaction by starvation. This correlates with our ealier observation that calmodulin appears not to fulfill a Ca 2ϩ -dependent regulatory function in microautophagy (Uttenweiler et al, 2005).…”
Section: Vtc Complex In Microautophagysupporting
confidence: 76%
See 4 more Smart Citations
“…Vtc-Cmd1p interaction by starvation. This correlates with our ealier observation that calmodulin appears not to fulfill a Ca 2ϩ -dependent regulatory function in microautophagy (Uttenweiler et al, 2005).…”
Section: Vtc Complex In Microautophagysupporting
confidence: 76%
“…Both Vtc2p, Vtc3p, and Vtc4p coimmunoprecipitated with Cmd1p ( Figure 7C) in the presence of the Ca 2ϩ chelator EGTA, but less in the presence of Ca 2ϩ . In line with this, microautophagic uptake in vitro was stimulated by EGTA and inhibited by Ca 2ϩ (Uttenweiler et al, 2005 and data not shown). We also tested if the interaction between the Vtc proteins and Cmd1p is regulated by starvation.…”
supporting
confidence: 61%
See 3 more Smart Citations